Biochemical and Histopathological effects of Acetaminophen and Protective Effects of Naringin on Liver Rats - Aryaf Mahmood Sabea; Ahlam J. H. AlKhamas; Bashar Sabah Sahib; Jawad Kadhim Faris (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted to find out liver protective activity of naringin (NRG) 40-80 mg/kg body weight(b.w.) against acetaminophen (ACN) 2g/kg induced liver damage in rats. Thirty two male rats were dividedinto four groups : group1: negative control, (1 ml/kg Saline orally) group II: positive control ACN (2g/kg), orally as single dose at first day, group III: ACN (2g/kg), orally as single dose at first day , plus NRG(40 mg//kg) orally for (8) consecutive days, group IV: ACN (2g/kg), orally as single dose at first day , plusNRG (80 mg//kg) orally for (8) consecutive days. All the rats were anesthetized to collect blood then killedon the (9) day of the experiment to take the liver samples. ACN induced liver damage was proved by asignificant (P<0.01) reduction in the body weight , total protein (TP) , albumin (AB) , superoxide dismutase(SOD) and catalase (CAT) enzymes and a significant (P<0.01) increased in liver weight, serum aspartatetransaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), total bilirubin (TB), directbilirubin (DB) , malondialdehyde enzyme (MAD) and histopathological changes. Protective liver toxicityeffect and oxidative damage caused by ACN significantly (P<0.01) increasing in body weight, TP, AB ,SODand CAT and significantly (P<0.01) decreasing in liver weight , AST, ALT, ALP, TB, DB and MAD andimproving tissue morphology by a meliorative in NRG 40 , 80 mg/kg b.w. These results confirm that NRGantioxidant effects can protect ACN induced hepatic toxicity in rats.